How to make things faster : lessons in performance from technology and everyday life - Millsap, Cary V. (O'Reilly Media, Inc., 2023)
Slow systems are frustrating. They waste time and money. But making consistently great decisions about performance can be easy, if you understand what's going on. This book explains in a clear and thoughtful voice why systems perform the way they do. It's for anybody who's curious about how computer programs and other processes use their time and about what you can do to improve them. Through a mix of personal vignettes and technical use cases, Cary Millsap reviews the process of improving performance and provides best practices for optimizing systems efficiently. You'll learn how to identify the information needed to improve a system, how to find the root causes of performance issues, and how to fix them. You'll also learn how performance optimization is both a skill set and a mindset, and how to develop both over time. If you're a computer professional whose success relies on software that goes fast, by the end of this book you'll be able to identify, view, scope, analyze, and remedy performance issues with consistency and confidence.